Development of safety science in Chinese higher education. (July 2018) - Zhang, Jiangshi; Fu, Jing; Hao, Hongyu; Chen, Na; Zhang, Wenyue; Kim, Young-Chan
Highlights: An overview of safety discipline in Chinese higher education institutions is provided. Curriculum provision of representative universities establishing safety discipline of different research fields was showed. The professional direction of safety science teachers is analyzed. Abstract: Safety science is a distinct, multidisciplinary activity in the academic community with abundant scientific connotation. Safety Science in China, especially in Chinese higher education, has developed rapidly in the past 20 years and its development process is affected by some factors including national laws and policies, economic development and administrative system. The above-mentioned factors make safety discipline with distinct industrial characteristics. In this paper, firstly, the development process and significant events of safety science in abroad and domestic is reviewed. Secondly, education condition about safety discipline in higher education institutions is analyzed, mainly including education institutes, research fields, curriculum provision, employment, vocational situation, and academic exchange. Then discussing how the three factors influence the development of safety discipline. The results show that 1999 is a demarcation point for the development process of safety science in China. Until 2016, there are 183 higher education institutions established safety discipline with different research fields. The focus of safety professionals' cultivation has gradually expanded from technical competence to the promotion of comprehensive ability and quality. Influenced by economy, the number of universities establishing safety discipline decreased from southeast coast to central region, to western region, and its research fields are basically consistent with the local prop industries. Furthermore, in order to solve the main problem of single industrial research field of safety discipline, Chinese universities should propose new research directions, improve discipline contents and make further efforts to soften the industrial effect of safety discipline.